2021
DOI: 10.3389/fpubh.2021.788370
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Mental Health Under COVID-19 Restrictions: A Mini Literature Review

Abstract: Coronavirus Disease 2019 (COVID-19) restrictions, including national lockdown, social distancing, compulsory quarantine, and organizational measures of remote working, are imposed in many countries and organizations to combat the coronavirus. The various restrictions have caused different impacts on the employees' mental health worldwide. The purpose of this mini-review is to investigate the impact of COVID-19 restrictions on employees' mental health across the world. We searched articles in Web of Science and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Items related to living with a partner or spouse, raising children or not and caring for elderly or other family members or not tended to inhibit research, but were not statistically significant. This survey did not include a mental health questionnaire, as in the previous study by Liu 2021 [ 27 ]. Since this survey was conducted in the early stages of the pandemic and at a time when there was no large-scale lockdown in Asia except for in China [ 28 ], it is possible that the impact of the pandemic had not yet manifested itself.…”
Section: Discussionmentioning
confidence: 99%
“…Items related to living with a partner or spouse, raising children or not and caring for elderly or other family members or not tended to inhibit research, but were not statistically significant. This survey did not include a mental health questionnaire, as in the previous study by Liu 2021 [ 27 ]. Since this survey was conducted in the early stages of the pandemic and at a time when there was no large-scale lockdown in Asia except for in China [ 28 ], it is possible that the impact of the pandemic had not yet manifested itself.…”
Section: Discussionmentioning
confidence: 99%
“…"4 Besides meeting fatigue, research confirms that stress, emotional exhaustion or distress, and anxiety and depression are psychological symptoms that are associated with remote working. 5,6 Meanwhile, a significant number of my family and friends work (at least partially) from home. It's just a personal observation, but many people seem to struggle more with stress or frustration while working remotely than when they worked in the office.…”
Section: The Dark Side Of Remote Workingmentioning
confidence: 99%
“…One reason for this interest is that employee mental health is increasingly prominent within workplaces, which leads to significant costs including absenteeism, burnout, employee compensation claims, work–family conflict and low productivity [ 2 , 3 ]. In particular, with the outbreak of COVID-19, the uncertainties and fears associated with the virus outbreak, along with survival crisis of enterprises, lead to increases in employees’ mental disorders [ 4 , 5 , 6 ]. For example, Xiong et al [ 7 ] found that people in China, Spain, Italy and five other countries had higher levels of symptoms of anxiety, depression, traumatic stress disorder and other mental health problems during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%